The application of the experiential learning approach in english as a secnd language at UDELAS University - Miranda S., Iliana Maribel (UDELAS, 2011)
This research focuses on the experiential learning approach and how it provides important advantages in the english teaching process. Learning a second language is becoming more important in a globalizing world.